Canonical correlation analysis of family burden of disease and quality of life in caregivers of people living with schizophrenia: evidence from Schizophrenia-specific cohort in the less-developed multi-ethnic region of Southwest China - Ximei Wang; Teng Zhang; Mingsong Li; Bo Yang; Liming Wang; Chuanwen Fu; Nishang Zhang; Zhengxu Li; Ce Yang; Zhimin Zhao; Qiong Meng; Yuemei Feng; et al. (BMC Psychiatry)
Abstract Background Health-related quality of life is a multi-dimensional concept that involves individual’s perceived physical and mental health, social relationships, and environment. Family members are the primary caregivers of people living with schizophrenia in China, the quality of life of caregiver of people living with schizophrenia is generally poorer, which may indirectly affect the quality of life of the people with schizophrenia. Methods We conducted a comprehensive survey on quality of life in caregivers of people living with schizophrenia based on the Schizophrenia-specific cohort in the Less-developed Multi-ethnic Region of Southwest China to validate the accessibility and effectiveness of the schizophrenia family care model at the family level, caregivers of people living with schizophrenia were selected as participants in Baoshan City, Yunnan Province from September 2022 to March 2023, quality of life, family burden of disease, sociodemographic and behavioral information of participants were collected. Results Domain scores for physical, psychological, social relationships, and environment of quality of life were 13.50 ± 2.61, 12.67 ± 2.40, 13.64 ± 2.32, and 12.46 ± 1.76 respectively. In our study, we found that gender, age, education level, personal monthly income, history of smoking and alcohol consumption, subjective sleep quality, relation to the patient, degree of self-care and the number of relapses in patient all influence 1 to 4 domains of quality of life for caregivers, stratified analysis was conducted to minimize the effect of gender on the results, we still found that history of smoking could positively predict the score of psychological domain and history of alcohol consumption could positively predict the score of social relationships domain. Canonical correlation analysis showed that the ‘impact on family interaction’ in family burden of disease was most closely related to quality of life. Conclusion Building harmonious family relationships can help improve the quality of life for caregivers of People living with schizophrenia.